Linking fatty acid derivatives with signalling and cross-talk in Pseudomonas aeruginosa - Palenzuela Bretones, Diana (2017)
Xanthomonas campestris is a bacterial plant pathogen that produces diffusible signal factor (DSF), a signalling fatty acid mediating the regulation of important pathogenicity traits, such as protease production and biofilm formation. The production of DSF is dependent on the activity of an enoyl CoA hydratase (ECH) enzyme. Chemically related long chain fatty acids, the DSF type (DSF T) molecules, have since been found to be produced by a large range of bacterial species including Stenotrophomonas maltophilia and Burkholderia cenocepacia, in which they have similar effects and are subject to a similar regulation. Interestingly, these molecules participate in inter species signalling as well, as they can affect the behaviour of species that do not produce them.